A study of the metallic silver dissolution with the MEA-NH3-Cu system - Reyes-Sandoval,Edith (2018)
ABSTRACT Leaching of silver from minerals has been studied for decades. Recently, research has been focused on the substitution of cyanide (because of its high toxicity) from hydrometallurgical operations. In this sense, the development of alternative-green leaching solutions for the recovery of metallic silver from minerals and urban mines is necessary. In this research, a thermodynamic-kinetic study of the alternative system “monoethanolamine (MEA)-ammonium sulfate-cupric sulfate” was performed for the dissolution of metallic silver, varying the pH and the cupric ion concentration at room temperature. Furthermore, this research aims to evaluate the silver dissolution behavior at a pH lower than 10.2, elucidating the rate determining step of the silver dissolution process at these conditions of pH and cupric ion concentration. Thermodynamic results confirm that the MEA and NH3 can complex silver generating the species: Ag(MEA)2+, AgMEA-, Ag(NH3)2+, AgNH3+ respectively. It was evaluated the effect of varying the pH (8.8, 9.9 and 9) and the cupric sulfate concentration (0.1, 0.15 and, 0.2 M at pH 9) on the kinetics of silver dissolution. The results revealed, the possibility to leach a 39% of silver using a leaching solution containing: 0.15 M cupric sulfate, 0.05 M MEA and 0.4 M ammonium sulfate at pH 9. The kinetic analysis showed that the silver dissolution is controlled by the diffusion of fluid species through a porous layer composed of copper oxides, which was ratified by SEM and EDS analysis. Finally the present paper, open the possibility to optimize the molar ratio MEA:NH3 to maximize the silver dissolution kinetics.